Employment effects of the new German minimum wage: Evidence from establishment-level micro data - Mario Bossler; Hans-Dieter Gerner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In Germany a new statutory minimum wage of exteuro 8.50 per hour of work was introduced on 1 January 2015. We identify employment effects using variation in the establishment-level affectedness. The data allow addressing anticipatory wage adjustments as well as spillover effects within and across workplaces. Difference-in-differences estimation reveals an increase in average wages by 4.8 percent and an employment reduction by about 1.9 percent in affected establishments. These estimates imply an employment elasticity with respect to wages of about -0.3. Looking at the associated labor flows, the employment effect seems mostly driven by a reduction in hires but also by a small increase in separations. Moreover, the employment neutral turnover rate decreases. When analyzing alternative adjustment margins, we observe a reduction in the typical contracted working hours but no effects on freelance employment.
Keywords: C23; J23; J38; 330